Studying rhythm processing in speech through the lens of auditory-motor synchronization - Luo, Lu; Lu, Lingxi (Frontiers in Neuroscience, 2023)
Continuous speech is organized into a hierarchy of rhythms. Accurate processing of this rhythmic hierarchy through the interactions of auditory and motor systems is fundamental to speech perception and production. In this mini-review, we aim to evaluate the implementation of behavioral auditory-motor synchronization paradigms when studying rhythm processing in speech. First, we present an overview of the classic finger-tapping paradigm and its application in revealing differences in auditory-motor synchronization between the typical and clinical populations. Next, we highlight key findings on rhythm hierarchy processing in speech and non-speech stimuli from finger-tapping studies. Following this, we discuss the potential caveats of the finger-tapping paradigm and propose the speech-speech synchronization (SSS) task as a promising tool for future studies. Overall, we seek to raise interest in developing new methods to shed light on the neural mechanisms of speech processing.